(untitled) (Research, Society and Development, 2021)
Syphilis is a polymorphic, infectious and systemic disease, caused by the bacteria T. pallidum, considered a disease of compulsory notification. Early diagnosis is an important factor in its control, this is performed by combining clinical findings and laboratory tests. Molecular techniques help in the diagnosis, however, there is no consensus on which technique would is the most appropriate, because studies present divergences such as which gene should be used as target, what sequence of primer, extraction method and type of sample. This review sought to investigate, based on scientific evidence, the most effective molecular techniques in the detection of T. pallidum DNA. Therefore, a systematic review of the literature was conducted in the PubMed, Science Direct and Lilacs databases, using the descriptors "syphilis" and "PCR" and "diagnosis" and "molecular biology", selecting works published in the last ten years. The sample consisted of 10 articles. As for the study design, the clinical trial was 100% prevalent. As for the method used, variations were evidenced, 6 used Nested PCR, 5 real-time PCR and 4 conventional PCR, 5 used more than one variation. The difference between them, such as time to evaluate a reaction, chance of contamination, reproducibility, specificity, sensitivity, precision and diagnostic accuracy, showed that the two genes of greatest interest are pol A and tpp47. Molecular tests, in particular nested PCR, proved to be promising, with good sensitivity and specificity in the diagnosis of syphilis together with serology to avoid clinical complications and disease transmission.